Gastroprotection studies of Schiff Base Zinc (II) derivative complex against acute superficial hemorrhagic mucosal lesions in rats - Golbabapour, S.; Gwaram, N.S.; Hassandarvish, P.; Hajrezaie, M.; Kamalidehghan, B.; Abdulla, M.A.; Ali, H.M.; Hadi, A.H.A.; Majid, N.A. (Public Library of Science, 2013)
Background: The study was carried out to assess the gastroprotective effect of the zinc (II) complex against ethanol-induced acute hemorrhagic lesions in rats. Methodology/Principal Finding: The animals received their respective pre-treatments dissolved in tween 20 (5% v/v), orally. Ethanol (95% v/v) was orally administrated to induce superficial hemorrhagic mucosal lesions. Omeprazole (5.79061025 M/kg) was used as a reference medicine. The pre-treatment with the zinc (II) complex (2.18161025 and 4.36261025 M/kg) protected the gastric mucosa similar to the reference control. They significantly increased the activity levels of nitric oxide, catalase, superoxide dismutase, glutathione and prostaglandin E2, and decreased the level of malondialdehyde. The histology assessments confirmed the protection through remarkable reduction of mucosal lesions and increased the production of gastric mucosa. Immunohistochemistry and western blot analysis indicated that the complex might induced Hsp70 up-regulation and Bax down-regulation. The complex moderately increased the gastroprotectiveness in fine fettle. The acute toxicity approved the non-toxic characteristic of the complex(<87.24161025 M/kg). Conclusion/Significance: The gastroprotective effect of the zinc (II) complex was mainly through its antioxidant activity, enzymatic stimulation of prostaglandins E2, and up-regulation of Hsp70. The gastric wall mucus was also a remarkable protective mechanism.